2021
DOI: 10.1177/1535370221995207
|View full text |Cite
|
Sign up to set email alerts
|

Fetuin-A exerts a protective effect against experimentally induced intestinal ischemia/reperfusion by suppressing autophagic cell death

Abstract: Intestinal tissue is highly susceptible to ischemia/reperfusion injury in many hazardous health conditions. The anti-inflammatory and antioxidant glycoprotein fetuin-A showed efficacy in cerebral ischemic injury; however, its protective role against intestinal ischemia/reperfusion remains elusive. Therefore, this study investigated the protective role of fetuin-A supplementation against intestinal structural changes and dysfunction in a rat model of intestinal ischemia/reperfusion. We equally divided 72 male r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Previous studies have revealed that Fetuin-A attenuates the inflammatory response and protects against injury in cerebral ischemia, intestinal ischemia/reperfusion and hereditary angioedema [ 38 , 48 , 49 ]. And according to our GO analysis, Fetuin-A is predicted to be involved in the biological processes of “acute phase response” and “inflammation”.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that Fetuin-A attenuates the inflammatory response and protects against injury in cerebral ischemia, intestinal ischemia/reperfusion and hereditary angioedema [ 38 , 48 , 49 ]. And according to our GO analysis, Fetuin-A is predicted to be involved in the biological processes of “acute phase response” and “inflammation”.…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal epithelium is most sensitive to IRI ( 9 , 10 ) and thus its integrity is decisive for the fate of the patient. As the barrier between the gut lumen and the rest of the organism, it is a critical factor for the systemic health of the whole organism and thus the outcome of intestinal IRI.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies proposed that the grade of autophagy might be crucial for the cellular survival in the course of IRI ( 31 35 ). However, there are controversial results whether autophagy is beneficial or detrimental in IRI ( 9 , 36 40 ). Due to the complete lack of nutrients, an activation of AMPK and thus autophagy is more likely to happen (faster) in no flow ischemia, whereas in low flow conditions the activation of AMPK may be postponed or completely abolished, possibly causing differing rates of autophagy under the different conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that fetuin-A attenuates the in ammatory response and protects against injury in cerebral ischemia, intestinal ischemia/reperfusion and hereditary angioedema [35,43,44]. And fetuin-A is involved in the biological processes of "acute-phase response" and "in ammation" according to our GO analysis.…”
Section: Discussionmentioning
confidence: 71%